Robot-assisted total hip arthroplasty. (2nd January 2016) - Banerjee, Samik; Cherian, Jeffery J.; Elmallah, Randa K; Pierce, Todd P.; Jauregui, Julio J.; Mont, Michael A.
Abstract : Precise and accurate biomechanical reconstruction during total hip arthroplasty (THA) is essential for durable long-term survivorship. Accurate fit of cementless hip implants is also crucial to reduce micromotion between the bone-implant interfaces to allow for stable osseointegration. Robotic technology aims to minimize potential human errors and improve implant alignment and fit, and address persisting concerns with modern-day cementless THA. Although robotic THA dates back to the early 1990s, concerns with increased operating times, costs, and complications led to its withdrawal. However, semi-active systems have renewed interest in robot-assisted joint arthroplasty. We reviewed the current technology, its potential benefits, and the reported clinical and radiographic outcomes. Early evidence suggests that robotic use may lead to more accurate reconstruction of radiographic parameters, such as implant positioning, fit, center-of-rotation, and leg-length discrepancy. Further research is needed to determine if these will translate into better outcomes and improved implant longevity to justify increased costs.